CURRICULUM MANAGEMENT IN PESANTREN (ISLAMIC BOARDING SCHOOL) IN THE SOCIETY 5.0 ERA AT DARUNNAJAH JAKARTA ISLAMIC BOARDING SCHOOL - Elita Fauzia; Muh Zuhdi; Maftuhah (Jurnal Isema : Islamic Educational Management, 2025)
Curriculum management in Islamic boarding schools (Pesantren) in the era of Society 5.0 involves balancing traditional Islamic values with the need for modern competencies. Society 5.0 promotes the use of digital technology to enhance human well-being, offering Pesantren opportunities to innovate without losing their religious identity. This study examines how Pesantren Darunnajah manages its curriculum to address these demands. Using an exploratory qualitative approach, data were gathered through observation, interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The findings show that the Pesantren upholds core principles panca jiwa, panca bina, and panca dharma as the foundation for character development. Its curriculum integrates three systems: Tarbiyatul Mu’allimin wal Mu’allimat Al-Islamiyah (TMI), the Modern Boarding School System, and the Madrasah System. Curriculum management follows stages of planning, development, implementation, evaluation, and follow-up. To respond to Society 5.0, the Pesantren integrates technology in learning, develops competency-based curricula, strengthens social emotional skills, collaborates with external institutions, and reinforces Islamic values. Overall, the study highlights the Pesantren’s ability to adapt to contemporary challenges while maintaining its identity and educational relevance.